Transit Migration: An Unnoticed Area in Ethnomusicology - Hikmet Öğüt, Evrim (Lidé města, 2015)
As a result of the expanding human mobilization in the today’s world due to wars, workforce markets, etc., the scope of migration and diaspora studies has increased in many areas. This is also true for musical studies, where a growing body of literature has been produced about these issues. However, by focusing mainly on settled communities and their musical productions, such as hybrid genres and forms created in the destination land, this literature does not adequately cover “transit migration”. Transit migration, being a particular type of human mobility, refers to the migration that includes at least three or more steps. This means that transit migrants do not permanently inhabit the land they firstly enter as migrants, but are supposed to stay in this transit country for a while and then continue their journey in order to reach a final destination point. In this article, I deal with this specific type of migration based on my intense field study on the Chaldean-Iraqi migrant community in Istanbul. The Chaldean community in Iraq, as a religious minority, is one of the most affected groups in the ongoing situation in Iraq, especially after the US invasion in 2003. Turkey functions as a transit country on their way to their prospective destination points, mainly including the US, Canada, and Australia. While dealing with the role of music during the indefinite time period that the participants are in the process of being temporary inhabitants in a foreign land, the applicability of the theoretical concepts of permanent migration to temporary migration is also discussed.